Survey on security and privacy issues of Wireless Sensor Network (International Journal of Engineering and Computer Science, 2018)
Proliferation of Wireless sensor network is increased. Security, how to localized sensor between two nodes, efficient authentication, privacy, scalability, flexibility and availability, these are main issues of wireless sensor network. Clustering based wireless sensor network will solve the problem of security, privacy issues and scalability.